Favorable outcome of empagliflozin treatment in two pediatric glycogen storage disease type 1b patients - Hexner-Erlichman, Zufit; Veiga-da-Cunha, Maria; Zehavi, Yoav; Vadasz, Zahava; Sabag, Adi D.; Tatour, Sameh; Spiegel, Ronen (Frontiers in Pediatrics, 2022)
Background Glycogen storage disease type 1b (GSD1b) is an ultra-rare autosomal recessive disorder, caused by mutations in SLC37A4 gene. Affected patients present with episodes of fasting hypoglycemia and lactic acidosis, hepatomegaly, growth retardation, hyperlipidemia and renal impairment. In addition, patients present neutropenia, neutrophil dysfunction and oral, and skin infections as well as a significant predisposition to develop inflammatory bowel disease (IBD). Low neutrophil counts and function is related to the toxic accumulation of 1,5-anhydroglucitol-6-phosphate (1,5-AG6P). Recently, several reports have shown that off-label treatment with empagliflozin (EMPA), an inhibitor of the renal glucose transporter SGLT2, decreased blood 1,5-anhydroglucitol (1,5-AG), and neutrophil 1,5-AG6P, thus resulting in a new therapeutic option for neutropenia and neutrophil dysfunction in patients. Methods Off-label treatment with EMPA was established in two GSD1b patients after signed informed consent. The patients were followed clinically. We monitored neutrophil counts and function, 1,5-AG levels in plasma and its renal clearance before and during EMPA treatment. Results A 17 year-old girl who had long standing oral ulcers and developed IBD, requiring systemic steroid and regular granulocyte colony-stimulating factor (GCSF) therapy and an 8 year-old boy who had steady non healing oral lesions were treated with empagliflozin during 18–24 months. Treatment led to increase of neutrophil counts and function with substantial clinical improvement. This included remission of IBD in the first patient which allowed to discontinue both GCSF and steroid therapy and resolution of oral lesions in both patients. The concentration of 1,5-AG in blood was greatly decreased within two weeks of treatment and remained stable thereafter. Conclusions Repurposing of empagliflozin to treat neutropenia in two GSD1b patients was safe and resulted in the urinary excretion of 1,5-AG, the normalization of neutrophil function, and a remarkable improvement of neutropenia-related clinical traits. We showed for the first time that empagliflozin increases concomitantly the renal clearance of both 1,5-anhydroglucitol and glucose in GSD1b patients.